Transfer of Land and Building Taxes in the Plantation and Forestry Sector in Indonesia in a SWOT Analysis Review - Nastiti Tri Sandy; Inayati Inayati (Universitas Teuku Umar, 2022)
Indonesia is a country that has high natural resource potential. This potential encourages the government to collect the tax on land and building plantations, forestry, mining, and other sectors (PBB-P3). Then the proceeds are allocated to local governments to overcome vertical fiscal inequality. However, in practice, problems were found related to the low fiscal independence of regions due to dependence on Transfers to Regions (TKD) by the central government and the distribution of Revenue Sharing Funds (DBH) on Land and Building Taxes and natural resources. This paper analyzes the strengths, weaknesses, opportunities, and threats of Land and Building Tax (PBB) in the Plantation and Forestry sector devolution from the central tax to local taxes. Also, analyze the strategies for the transfer of PBB plantation and forestry sector. This study uses a qualitative approach with SWOT analysis and primary collection techniques through in-depth interview data and literature study. The analysis results show that PBB plantation and forestry sector has several weaknesses and threats related to the readiness of local government human resources, the mechanism for collecting PBB-P3, and the impact on the exploitation of natural resources. However, the strengths and opportunities found in this study can be considered for the regionalization of PBB plantation and forestry sector in the future. Strength-opportunity, strength-threat, weakness-opportunity, and weakness-threat strategies that can be prepared are preparing local government human resources, technological facilities for PBB-P3 administration, and special rules governing PBB-P3 regionalization.